Amino Acids Hydrolyzed from Animal Carcasses Are a Good Additive for the Production of Bio-organic Fertilizer - Liu, Hongjun; Chen, Dandan; Zhang, Ruifu; Hang, Xinnan; Li, Rong; Shen, Qirong (Frontiers in Microbiology, 2016)
High-quality bio-organic fertilizers (BIOs) cannot be produced without the addition of some proteins. In this study, compound liquid amino acids (CLAA) from animal carcasses were utilized as additives into matured composts to create novel BIOs containing plant growth-promoting rhizobacteria (PGPR). The results showed that adding CLAA and inoculating bacteria meanwhile resulted in failed solid-state fermentation (SSF) due to the higher H+ contents. While after pre-compost for 4 days before PGPR inoculation, treatments of matured chicken or pig manure added with 0.2 ml g-1 of CLAA resulted in a maximum biomass of functional strains. Illumine-MiSeq sequencing and Real-Time PCR results showed that the CLAA addition decreased the bacterial abundance and richness, altered the bacterial community structure and changed the relative abundance of some microbial groups. This study offers a high value-added utilization of waste protein resources for producing economical, high-quality BIO.